Mitral Valve Repair with a Biodegradable Annuloplasty Ring for Mitral Regurgitation - Zorman, Yilmaz; IŞIK, Bekir; YILMAZER , Mustafa Serdar; AKSOY, Tamer (Journal of Humanitarian Cardiovascular Medicine, 2023)
Objective: We aimed to evaluate the effectiveness of the mitral valve repair procedure using biodegradable ring implantation to treat severe mitral valve regurgitation. Method: Between May 2007 and 2009, 23 patients without mitral stenosis underwent mitral valve repair using a biodegradable annuloplasty ring. 3 of the 23 patients are excluded from the study due to discontinuation of follow-up. Preoperative, postoperative 7th day, 3rd month, 6th month, and 1st-year echocardiographic data of 20 patients were collected retrospectively and statistically analyzed with Chi-square and Student T-tests. Results: At follow-up, transthoracic echocardiography revealed no or trivial regurgitation. Although there was an increase in the mean gradient during the early postoperative period (7th days and 3rd months), there was no statistically significant difference in the mean gradient between the preoperative and late postoperative period (6th month and 1st year). Mean gradients were 3.48±0.64, 2.72±0.31, 2.62±0.25, and 2.58±0.21 mmHg, respectively at 7th days, 3rd months, 6th months, and 1st year. Increased preload due to mitral regurgitation resulted in larger left ventricular end-diastolic volume (LVEDV) and left ventricular end-systolic volume (LVESV) preoperatively of 194.42±21.39 ml (range, 245.00 to 165.00 ml) and 94.23±36.59 ml (range, 203.35 to 52.80 ml) respectively. The decrease in mean LVEDV and LVESV at 1 year was statistically significant, 130.40±11.04 ml (range, 145.00 to 115.00 ml; p<0.001) and 64.21±13.20 ml (range, 80.08 to 40.25 ml; p<0.001), respectively. Additionally, left ventricular ejection fraction (LVEF) reaches the preoperative value (%51.15±14.04) in the 6th month (%51.58±7.32), although there is a decline in the early postoperative period (%47.11±11.22 on 7th day and 46.35±8.03 in 3rd month). One late death occurred. Mitral valve re-operation was necessary for one rheumatic patient. Conclusion: Annuloplasty using a biodegradable mitral ring has shown desired long-term outcomes with particular advantages compared to traditional annuloplasty rings.